Generalized infection with unknown starting point in children hospitalized in a district hospital - Jankowska, Paula; Jankowski, Krzysztof; Kamiński, Piotr; Rudnicka-Drożak, Ewa (Journal of Education, Health and Sport, 2019)
IntroductionInfection is the most common cause of children medical consultations. Often the clinical picture of the patient is disproportionate to the results of laboratory tests which may indicate for generalized infection.Case reportsCase 1: A 4-year-old patient admitted to the Department due to a fever 39˚C lasting from 2 days and periodic abdominal pain. Good general condition, throat slightly red. In laboratory studies, procalcitonin 44.5 ng/ml, CRP 121.5 mg/dl, WBC 15.32 ths/ul. Empirical treatment with ceftriaxone and vancomycin was included. Blood cultures, Staphylococcus hominis MLSB, MRCNS. Case 2: A patient nearly 5 years old admitted to the Department due to a fever 39.5˚C. In outpatient examinations CRP 41 mg/dl, WBC 39 ths/ul. Physical examination: reddening of throat mucosa, palatine tonsils slightly enlarged, reddish, without rash. In laboratory tests CRP 95 mg/dl, WBC 41.95 ths/ul, PCT 1.19 ng/ml. On the second day of hospitalization, an increase in inflammatory markers was observed (PCT 1.47 ng/ml, CRP 235.7 mg/dl). Vancomycin was added. Case3: 18-month-old boy admitted to the Department due to fever 40.5˚C. Good general condition, throat slightly reddened, occasional cough. In laboratory tests PCT 8.07 ng/ml. Empirical antibiotic therapy with ceftriaxone was implemented. Due to persistence of fever up to 39.5˚C - control tests of PCT 10.03 ng / ml. Vancomycin was implemented. Urine culture negative, in blood culture the present growth of Staphylococcus warneri. ConclusionsIt is extremely important to be vigilant in case of feverish children. Sometimes, despite a good general condition and no significant abnormalities in a physical examination, we can deal with generalized infection.